Role of social media in delivering medical knowledge to people of Pakistan - Aziz, Azhan; Ejaz Ahsan, Nida; Shahid, Muhammad (Journal of the Pakistan Medical Association, 2026)
Social media is an effective communication medium on a global scale which plays its role in promoting knowledge1. In developing countries like Pakistan, where traditional methods such as newspapers and local channels are becoming increasingly obsolete, social media offers valuable information and acts as the primary source of information. The statistics from July 2021 state that approximately 57% of the global population is social media users1. When talking about Pakistan, the use of social media has had a surge, with about 180 million cellular users and 76.3 million internet users1. This substantial increase suggests that social media is a powerful tool and that it is used for knowledge delivery in Pakistan due to its accessibility among most of the population. According to a survey 60% doctors have reported that using social network has refined their professional skills2. Most scholars use social media for their research and statistical analysis3. Modern technology has helped patients of rural areas to manage blood sugar and get educated on type 2 Diabetes mellitus, which has solved their major issue of visiting the cities for regular checkup4. The Higher Education Commission instructed the educational institutes of Pakistan to adapt to this new digital change, in the curriculum, as a medium of communication for sharing knowledge among students and professors5. Review of publicly available YouTube content led to the identification of several channels providing credible information on various topics in Pakistan. One such channel is “Cardio TV”, which provides insights from top consultants about the management and treatment of cardio-metabolic disease. On the contrary, the credibility of information on social media remains a major issue.Lack of transparency in creating content makes it difficult for individuals to differentiate credible sources from unreliable sources. Furthermore, algorithms that tailor content to users' pre-existing beliefs can create echo chambers and distort perceptions of reality. This can be overcome by strengthening regulations and policies, promoting literacy and fact-checking practices among the users. To summarise, everything possesses its own set of pros and cons. The role of social media in delivering knowledge in our lives reflects our choices in utilizing this powerful tool. By allowing the advantages to outweigh the disadvantages of social media, developing countries can use social media to promote Public Health Campaigns, Medical Research and enhance the quality of life of their population.